PENGARUH MACAM MEDIA DAN KONSENTRASI PUPUK FERMENTASI AMPAS TAHU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolens L.) SECARA HIDROPONIK - Muji Rahayu; Samanhudi Samanhudi; A.S. Widodo (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
Title : The Effect of  Media Various and Concentration of Tofu Waste Fermentation Manure to Growth and Yield of Celery (Apium graveolens L.) by Hydroponic. Celery Apium graveolens L.) is a kind of leave vegetable which has a function to be an aroma addition in vegetables. This plant can grow in upland and low land. The best planting time at the first rain has fallen or the end of rain season. For to get continue yield, celery can cultured by hydroponic with use some plant media. Besides that, organic manure can used for increase plant growth and to get safety product. The aims of this research is to know the effect of the kind of media and manure concentration of tofu waste fermentation to growth and yield of celery plant that is planted in hydroponics media. The research was conducted from August until November 2007, at the Green House in Agriculture Faculty of Sebelas Maret University. The research used Complete Random Design (RAD) in factorial, it consists of two factors with three repeating. The first factor is manure concentration of tofu waste fermentation which consist of 0,00kg/l, 0,25 kg/l, 0,50 kg/l, 0,75 kg/l, 1,00 kg/l, and the concentration of 1,25 kg/l. The second factor is the kind of media which consist of sand media, husk charcoal media, and the mixing of sand and husk charcoal media. The result of the research showed that the use of sand and husk charcoal mixing produces the highest level of plant height, leave number, leave wide, wet and dry weight of straw. The treatment of 1 kg/l manure concentration given the best level of plant height, leaf number, leaf wide, root volume, as well as the weight of wet and dry weight of straw. The best combination for celery plant’s growth and development is in the combined of 1 kg/l manure concentration, with the plant media using the mixing of sand and husk charcoal. Key words: media, fermentation, manure of tofu, celery Apium graveolens L.), hydroponic